Impacto del cambio climático en plagas y enfermedades del agro - Miranda Galarza, Marian Annabelle (2024)
Based on the study developed on the topic “Impact of climate change on agricultural pests and diseases”, climate impact represents one of the great risks for the agricultural process worldwide, impacting not only crop production, but also in the increase in agricultural pests and diseases. This global phenomenon, attributed mainly to human activities, has altered climate patterns, generating conditions conducive to the proliferation of insects, fungi and bacteria harmful to crops, in which the general objective was raised; Determine the effect of climate change on agricultural pests and diseases. Based on the methodology, important and relevant data were collected from sources such as articles, scientific journals, theses, and books. The investigative work will be developed as a non-experimental study with a bibliographic design. In terms of results, research focused on identifying the effects of climate change on the dynamics of agricultural pests and diseases has yielded significant results that highlight the interconnection between climate change and crop health. There has been an evident increase in the periodicity and severity of agricultural pests in specific areas, directly attributable to the climatic changes registered in the region studied. In conclusion, an increase in the frequency and intensity of extreme weather events was observed, which has contributed to the emergence of conditions more conducive to the proliferation of harmful organisms.